2006
DOI: 10.1002/dc.20437
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the processing of bloody cervical specimens: Glacial acetic acid and the Thinprep® Pap test™

Abstract: Since the utilization of the ThinPrep Pap Test in clinical practice, laboratories have strived to optimize cellular yields from cervicovaginal samples. Bloody specimens that often hamper cytologic interpretation and/or render a specimen unsatisfactory for diagnosis on conventional smears also affect ThinPrep preparations. Currently, there is no uniformly utilized method for the processing of bloody cervical specimens sent for analysis by the ThinPrep method. The purpose of this study is to present the protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 7 publications
2
26
0
Order By: Relevance
“…24 Additional studies have further verified these findings and have shown that ThinPrep reprocessing of bloody cervical specimens with a GAC wash results in fewer unsatisfactory diagnoses and an improved ability to detect epithelial abnormalities that are not present on the unsatisfactory slide prior to reprocessing. [20][21][22]24 Bile duct brushings continue to be an important tool for the detection of pancreatic and bile duct abnormalities. Some of the more common methodologies for processing bile duct brushings include direct smears, cytospins, and ThinPrep technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Additional studies have further verified these findings and have shown that ThinPrep reprocessing of bloody cervical specimens with a GAC wash results in fewer unsatisfactory diagnoses and an improved ability to detect epithelial abnormalities that are not present on the unsatisfactory slide prior to reprocessing. [20][21][22]24 Bile duct brushings continue to be an important tool for the detection of pancreatic and bile duct abnormalities. Some of the more common methodologies for processing bile duct brushings include direct smears, cytospins, and ThinPrep technology.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that reprocessing bloody ThinPrep cervicovaginal specimens with glacial acetic acid wash increases sample adequacy and the detection rate of epithelial abnormalities. [19][20][21][22] However, there is little data describing whether a glacial acetic acid wash improves the slide cellularity and ability to detect malignancy when assessing pancreatobiliary tract brushings. The goal of this study was to determine whether the use of a glacial acetic acid washes prior to slide processing would increase the cellularity and improve the quality of pancreatobiliary tract slides.…”
mentioning
confidence: 98%
“…Each method offers ‘clean’ slides with proprietary methods for removing obscuring elements such as blood and inflammation. The ThinPrep method has been noted to have some difficulty in handling bloody samples as the filters become overwhelmed with blood [24,25]. This may be managed by reprocessing following a rinse with acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of specimens containing grossly visible blood with glacial acetic acid (GAA) is effective in reducing the unsatisfactory rate. 9,11,12,14,15 However, a subgroup of unsatisfactory specimen with too few squamous cells was identified with presence of microscopic red blood cells (TFSQRBC). In this study, we evaluated the effectiveness of reprocessing unsatisfactory TP specimens of TFSQRBC and the follow-up outcomes of these patients.…”
mentioning
confidence: 98%
“…The most frequent causes of unsatisfactory status in TP specimens are too few squamous cells, followed by obscuration of red blood cells, white blood cells, and mucin. [9][10][11][12][13][14][15] Because TP is a filter-based processing technique, non-squamous cell particles, such as white and red blood cells (RBC) and mucin, compete with squamous cells to adhere on the filter, which results in too few squamous cells on the slide. Pretreatment of specimens containing grossly visible blood with glacial acetic acid (GAA) is effective in reducing the unsatisfactory rate.…”
mentioning
confidence: 99%